Polyethylene waxes: catalytic synthesis by ti-biphenolates - Umare, Prashant S.; Rao, Karumanchi; Tembe, Gopal L.; Dhoble, Deepa Arun; Trivedi, Bhavna (Journal of Macromolecular Science Part A‐Pure and Applied Chemistry, 2007)
{Soluble complexes of Ti (IV) bearing biphenol groups such as 1,1'-binaphthelene 2, 2' diol (Binol), 1, 1'-methylene di-2-naphthol, biphenol were prepared and characterized. These catalyst precursors formulated as [
Keywords: fibers; Nanoparticles; Self-assembly